Assessing The Accuracy of Childrens’ Literature Translation Using the Angelelli Rubric - Lina Anisah; Ninuk Lustyantie; Fathiaty Murtadho (Yayasan Adra Karima Hubbi, 2024)
The primary objective of this study is to communicate the precision of the translation of the children's story presented in the Let's Read mobile application. Utilizing Angelelli's assessment rubric, the focus is on evaluating the accuracy of the translation of children's literature. Through a thorough analysis of the translation of the Indonesian story, the research unveils both strengths and weaknesses in the translation process, shedding light on the challenges encountered in adapting the text for young Indonesian readers. The research methodology involved is qualitative with content analysis approach, selecting the story of English and its Indonesian translation from the Let's Read mobile application. The translations were then assessed using Angelelli's scoring rubric. The findings contribute significantly to the ongoing discourse on the assessment of translation quality, particularly within the realm of children's literature. These results provide valuable insights for refining the translation process and enriching the reading experience for young users of the Let's Read mobile app. Additionally, the research underscores the importance of accurately conveying the meaning of source texts to preserve the educational and entertainment value of translated children's literature. It emphasizes the necessity for cultural sensitivity and adaptation to create captivating and relevant reading experiences for children from diverse backgrounds